1996
DOI: 10.1097/00000658-199608000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MAGE Genes in Human Colorectal Carcinoma

Abstract: ObjectiveThe human genes MAGE-1 and -3 encode tumor-specific peptide antigens, which are recognized by autologous cytotoxic T lymphocytes. The antigens coded by those genes may be useful for cancer immunotherapy. There is, however, little information on the expression of these genes in human colorectal carcinomas. MethodThe expression of MAGE-1, -2, and -3 genes in 54 pairs of tumor and corresponding normal tissue specimens of the colorectum was determined by means of reverse transcription polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 24 publications
(1 reference statement)
8
49
0
Order By: Relevance
“…For our investigations, we chose besides breast and prostate cancer cell lines different MAGE-negative cell lines HL60, Colo205, WiDr, and HepG2, whose MAGE-A gene expression has been shown not to be inducible despite extensive treatment with 5-aza-CdR (16)(17)(18)(19). In all cell lines tested with the exception of HepG2 cells, we were able to stimulate MAGE-A expression with the demethylating agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our investigations, we chose besides breast and prostate cancer cell lines different MAGE-negative cell lines HL60, Colo205, WiDr, and HepG2, whose MAGE-A gene expression has been shown not to be inducible despite extensive treatment with 5-aza-CdR (16)(17)(18)(19). In all cell lines tested with the exception of HepG2 cells, we were able to stimulate MAGE-A expression with the demethylating agent.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that both DNA hypermethylation and hypomethylation play a crucial role during tumorigenesis, and transcriptional activation might be induced by promoter demethylation. However, several laboratories have shown that although tumor cells were treated by the DNA methylase inhibitor 5-aza-2 ¶-deoxycytidine (5-aza-CdR) up-regulation of MAGE-A gene expression could not be always observed (2,(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the methylation status of the promoter region of GNG7 in oesophageal cancer, cell lines were treated with a demethylating drug, 5-AZAC, as in our previous study (Mori et al, 1996). We analysed GNG7 expression by quantitative RT-PCR before and after 5-AZAC treatment in 15 oesophageal cancer cell lines.…”
Section: -Azac Treatment Of Oesophageal Cancer Cell Linesmentioning
confidence: 99%
“…We previously reported that MAGE-1 and MAGE-3 genes were expressed in 62% and 57% of oesophageal carcinomas (Inoue et al, 1997), 41% and 38% of gastric carcinomas (Inoue et al, 1995), 30% and 20% of colorectal carcinomas (Mori et al, 1996), 24% and 31% of breast carcinomas , and more than 65% of hepatocellular carcinomas . We also identified some MAGE gene-encoded peptides recognized by CTL Fujie et al, 1999).…”
Section: Introductionmentioning
confidence: 95%